Insulin-like growth factor binding protein 1, Bishop score, and sonographic cervical length: tolerability and prediction of vaginal birth and vaginal birth within 24 hours following labour induction in nulliparous women - Vallikkannu, Narayanan; Lam, W.K.; Omar, Siti Zawiah; Tan, Peng Chiong (Wiley, 2016)
Objective: To evaluate the tolerability of cervical insulin-like growth factor binding protein 1 (IGFBP-1) and its value as a predictor of successful labour induction, compared with Bishop score and transvaginal ultrasound (TVUS) cervical length. Design: A prospective study. Setting: A tertiary hospital in Malaysia. Population: A cohort of 193 term nulliparous women with intact membranes. Methods: Prior to labour induction, cervical fluid was obtained via a vaginal speculum and tested for IGFBP-1, followed by TVUS and finally Bishop score. After each assessment the procedure-related pain was scored from 0 to 10. Cut-off values for Bishop score and cervical length were obtained from the receiver operating characteristic (ROC) curve. Multivariable logistic regression analysis was performed. Main outcomes measures: Vaginal delivery and vaginal delivery within 24 hours of starting induction. Results: Bedside IGFBP-1 testing is better tolerated than Bishop score, but is less well tolerated than TVUS [median (interquartile range) of pain scores: 5 (4–5) versus 6 (5–7) versus 3 (2–3), respectively; P < 0.001]. IGFBP-1 independently predicted vaginal delivery (adjusted odds ratio, AOR 5.5; 95% confidence interval, 95% CI 2.3–12.9) and vaginal delivery within 24 hours of induction (AOR 4.9; 95% CI 2.1–11.6) after controlling for Bishop score (≥4 or ≥5), cervical length (≤29 or ≤27 mm), and other significant characteristics for which the Bishop score and TVUS were not predictive of vaginal delivery after adjustment. IGFBP-1 has 81% sensitivity, 59% specificity, positive and negative predictive values of 82 and 58%, respectively, and positive and negative likelihood ratios of 2.0 and 0.3 for vaginal delivery, respectively. Conclusion: IGFBP-1 better predicted vaginal delivery than BS or TVUS, and may help guide decision making regarding labour induction in nulliparous women. Tweetable abstract: IGFBP-1: a stronger independent predictor of labour induction success than Bishop score or cervical sonography.